The The historical context and book culture of Pedro de Peralta y Barnuevo - Guibovich Pérez, Pedro M. (2024)
Recognized by his contemporaries as a scholar in different branches of literature and science, Pedro de Peralta y Barnuevo was the author of numerous works and an insatiable reader. In this text I study the circumstances and means that allowed him to access books and, therefore, cultivate reading: the instruction received at the University of San Marcos, the gatherings and academies in which he participated in Lima, and the book trade. existing in this city. As an active member of the Republic of colonial letters, Peralta must have accumulated an important collection of books throughout his life, but unfortunately only a partial record of it has come to us, thanks to the post-mortem inventory of his assets, carried out in 1743. Despite its limitations, this inventory is a historical source of exceptional interest because it confirms Peralta's encyclopedic curiosity and allows us to reconstruct the historical context that made it possible. In the final part of this essay, I transcribe said list of books and propose the respective identifications.